2014
DOI: 10.1681/asn.2013050482
|View full text |Cite
|
Sign up to set email alerts
|

HDL Cholesterol Is Not Associated with Lower Mortality in Patients with Kidney Dysfunction

Abstract: In the general population, HDL cholesterol (HDL-C) is associated with reduced cardiovascular events. However, recent experimental data suggest that the vascular effects of HDL can be heterogeneous. We examined the association of HDL-C with all-cause and cardiovascular mortality in the Ludwigshafen Risk and Cardiovascular Health study comprising 3307 patients undergoing coronary angiography. Patients were followed for a median of 9.9 years. Estimated GFR (eGFR) was calculated using the Chronic Kidney Disease Ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
60
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 32 publications
6
60
0
3
Order By: Relevance
“…Recent studies have shown an association of HDL-cholesterol levels as predictors of CKD progression, but not with CVD risk. [40][41][42] This is in line with our findings that KTx good patients have higher HDL-cholesterol levels compared with KTx poor patients (Table 1), which is likely a consequence of recovered renal function. A major finding of our study is that functional properties of HDL remain compromised after renal transplantation, shown by substantial impairments in both KTx groups similar to patients with ESRD.…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies have shown an association of HDL-cholesterol levels as predictors of CKD progression, but not with CVD risk. [40][41][42] This is in line with our findings that KTx good patients have higher HDL-cholesterol levels compared with KTx poor patients (Table 1), which is likely a consequence of recovered renal function. A major finding of our study is that functional properties of HDL remain compromised after renal transplantation, shown by substantial impairments in both KTx groups similar to patients with ESRD.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, there is evidence that increased oxidized ApoAI levels are associated with a high risk of cardiovascular mortality in hemodialysis patients (120). The clinical significance of the above mentioned abnormalities are highlighted in recent studies that have shown the association of elevated serum HDL cholesterol levels with improved CV mortality is significantly diminished in patients with reduced estimated GFR (121). In addition, we have shown that in patients with ESRD on maintenance hemodialysis, reduced serum triglyceride to HDL ratio and elevated serum HDL cholesterol levels were paradoxically associated with increased CV and all-cause mortality (122).…”
Section: Alterations In High Density Lipoprotein Metabolismmentioning
confidence: 71%
“…A recent study in a large cohort of U.S. veterans found that the lowest and highest deciles of serum HDL cholesterol levels were associated with significantly increased risks of incidence and progression of CKD (123). Hence, elevated serum HDL cholesterol concentrations are not necessarily associated with improved outcomes in patients with CKD (121). This combined with the fact that HDL from patients with CKD/ESRD on maintenance hemodialysis has been shown to have impaired reverse cholesterol transport capabilities that can lead to HDL dysfunction and account for the paradoxical associations of serum HDL level with outcomes noted in epidemiologic studies (124,125).…”
Section: Alterations In High Density Lipoprotein Metabolismmentioning
confidence: 99%
“…26 HDL is a complex particle and blood levels of HDL cholesterol do not reflect its diverse vascular protective functions. In CKD, HDL carries a distinct protein cargo with acute phase protein serum amyloid A1, apoCIII, and lipoprotein-associated phospholipase A2.…”
Section: Discussionmentioning
confidence: 99%